Modulation of Serum Brain-Derived Neurotrophic Factor by a Single Dose of Ayahuasca: Observation From a Randomized Controlled Trial - Almeida, Raíssa Nóbrega de; Galvão, Ana Cecília de Menezes; da Silva, Flávia Santos; Silva, Erick Allan dos Santos; Palhano-Fontes, Fernanda; Maia-de-Oliveira, João Paulo; de Araújo, Lobão-Soares Barros; Lobão-Soares, Bruno; Galvão-Coelho, Nicole Leite (Frontiers in Psychology, 2019)
Serotonergic psychedelics are emerging as potential antidepressant treatment tools, as suggested in a recent randomized controlled trial with ayahuasca for treatment-resistant depression. Preclinical and clinical studies have shown that serum brain-derived neurotrophic factor (BDNF) levels increase after treatment with serotoninergic antidepressants. However, the exact role of BDNF as a biomarker for diagnostic and treatment of major depression needs to be better explored. In this study, registered at http://clinicaltrials.gov (NCT02914769), we investigated serum BDNF levels in healthy controls (N= 45) and patients with treatment resistant depression (N = 28), before (baseline) and 48 hours after (D2) a single dose of ayahuasca or placebo. We found similar baseline levels of serum BDNF in both patients and healthy individuals. We detected lower levels of BDNF at baseline in a subgroup of subjects who also presented hipocortisolemia, with respect to individuals with eucortisolemia. Moreover, we found a baseline negative correlation between BDNF and serum cortisol in volunteers with eucortisolemia. After treatment (D2) we observed higher BDNF levels in both patients and controls that ingested ayahuasca (N= 35) when compared to placebo (N= 34). Moreover, in D2 just patients treated with ayahuasca (N= 14), and not with placebo (N= 14), presented a significant negative correlation between serum BDNF levels and depressive symptoms (MADRS scores). Few previous randomized controlled trials have evaluated serum BDNF levels in response to antidepressant treatments and their results are not conclusive. This is the first clinical trial to explore the modulation of BDNF in response to a psychedelic with antidepressant potential, and the results suggest a potential link between the observed antidepressant effects of ayahuasca and changes in serum BDNF, which contributes to the emerging view of using psychedelic substances in the treatment of resistant depression.